Evaluating MCU Pharmacy Graduates' Board Exam Success and Gaps: Insights from 2019-2024 - Batu, Karina Marie (JPAIR Multidisciplinary Research, 2025)
Maintaining strong board examination performance is crucial for pharmacy schools as it signifies educational excellence and graduates' readiness for professional practice. This study examines the performance trends of Manila Central University (MCU)-College of Pharmacy graduates from 2019 to 2024, focusing on the comparison between their success in the first attempt immediately after graduation and in subsequent attempts. The study aims to uncover the factors contributing to these performance outcomes and propose strategies to enhance student success in the licensure exams. Using a descriptive phenomenological approach and documentary analysis, the research investigated the experiences of twenty MCU pharmacy graduates who took the pharmacist licensure examination (PLE) multiple times within the specified period. Colaizzi's method of phenomenological analysis was employed to extract and categorize significant statements from participants' lived experiences. Three main themes emerged as key contributors to higher success rates on the first attempt: Recency of Knowledge, Dedicated Review Period, and Strong Support System. Additionally, selections cited Lack of Confidence and Lack of Focus as factors affecting their subsequent examination attempts. The study proposes several strategies to improve board exam outcomes, including integrating exam preparation into the curriculum, strengthening review programs, enhancing psychological and emotional resilience, and fostering mentorship from faculty and alumni.
Keywords: Social Science; Board examination; descriptive phenomenological design; Philippines